Pengaruh Dimensi e-WOM terhadap Minat Beli Konsumen (Studi pada Pengguna Aplikasi Shopee di Kota Kendari) - Yusuf Yusuf (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The research was conducted to determine the influence of e-WOM Credibility, e-WOM Quality and e-WOM Quantity on buying interest in Shopee application users in Kendari City. The samples used were 80 samples with the criteria of being 15 years old and above. The sampling technique Accidental sampling, which is a sampling technique based on chance, that is, anyone who happens to meet a researcher, can be used as a sample, if it is seen that the person who happens to meet is suitable as a data source. The researcher used a quantitative approach using multiple linear regression analysis with the help of the IBM 23 version of the SPSS program. The results of this study show that the e-WOM Credibility variable (X1) has a positive and significant effect on the buying interest of Shopee application users in Kendari City (Y), the e-WOM Quality (X2) variable has a positive and significant effect on the buying interest of Shopee application users in Kendari City (Y), the e-WOM Quantity (X3) variable has a positive and significant effect on the buying interest of Shopee application users in Kendari City (Y) e-WOM Credibility, e-WOM Quality and e-WOM Quantity simultaneously have a positive and significant effect on the buying interest of Shopee application users in Kendari City.